SCALES AND OTOLITHS OF THE ’KOTH’ OTOLITHOIDES BRUNNEUS (DAY) AS AGE INDICATORS - Kutty, M Narayanan (Indian Journal of Fisheries, 2011)
GROWTH RINGS on the scales and otoUths of ’Koth’ have been recorded byKarandikar and Thakur (1951). Mention of growth checks on the scalesof this fish and their probable utility in -age determination has also beenmade by Seshappa (unpublished). Studies on the scales and otoliths of’Koth’ from the local ’dol’ net catches landed at Bombay and the catchesof the trawlers working along the Bombay coast were begun by the authorin February 1958 with a view to assess their value in age determination ofthe fish. Material for the present study was also collected subsequentlyfrom the gill-net catches at Bedi in the Gulf of Cutch.